2020
DOI: 10.5430/wje.v10n3p113
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Opinions about the Distance Education to Art and Design Courses in the Pandemic Process

Abstract: This research was carried out to determine student views on distance education through art and design courses. The study group of the research consists of 45 undergraduate students studying at different faculties of İzmir Katip Çelebi University in Turkey during the spring semester of the 2019-2020 academic year. The focus of the article is to determine the effect of distance education, which is carried out suddenly, on students' perceptions of art lesson. A semi-structured interview technique was performed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 26 publications
4
52
0
23
Order By: Relevance
“…Similar preferences for use of these distance learning platforms have been reported in other studies in the literature [18,20]. How to use such technology sufficiently and effectively has been cited as one of the main challenges in the pandemic for both educators and students [1,18]. One of the key findings of this study was that our participants already had training on the use of a variety of technology software and the flipped classroom model.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Similar preferences for use of these distance learning platforms have been reported in other studies in the literature [18,20]. How to use such technology sufficiently and effectively has been cited as one of the main challenges in the pandemic for both educators and students [1,18]. One of the key findings of this study was that our participants already had training on the use of a variety of technology software and the flipped classroom model.…”
Section: Discussionsupporting
confidence: 75%
“…All teachers interviewed reported that their schools made a rapid transition to a mix of distance learning and paper packets. Though some considered this shift to be necessary and important for the continuity of student learning [1,11,12], many other practicing educators reported that the shift was abrupt, difficult, haphazard, and left them unprepared [1][2][3]13]. The shift was especially challenging for those who were in areas without adequate distance learning infrastructure and Internet access.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations